Common peroneal nerve rupture with multiple ligament knee injury: A case report. Issue 7 (11th July 2022) - Tada, Kaoru; Matsuta, Masashi; Akahane, Mika; Murai, Atsuro; Tsuchiya, Hiroyuki
Abstract: In peroneal nerve palsy with closed knee injury, most of the case improves by follow‐up. We present a case of peroneal nerve rupture with closed multiple ligament knee injury, requiring nerve transplantation. In multiple ligament knee injury, it is necessary to consider the possibility of peroneal nerve rupture. Abstract : Even if due to low‐energy trauma, peroneal nerve rupture may occur in patients with multiple ligament knee injury.